Effects of dietary methanolic extract of hyssop, Hyssopus officinalis, on growth performance, hepatic antioxidant, humoral and intestinal immunity, and intestinal bacteria of rainbow trout, Oncorhynchus mykiss - Morteza Yousefi; Seyyed Morteza Hoseini; Behrooz Abtahi; Yury Anatolyevich Vatnikov; Evgeny Vladimirovich Kulikov; Natalya Yurievna Rodionova (Frontiers in Marine Science, 2022)
The aims of the present study were to assess the effects of Hyssop, Hyssopus officinalis, methanolic extract (HE) on growth performance, hepatic oxidative status, humoral and intestinal immunity, and intestinal bacteria of rainbow trout, Oncorhynchus mykiss. Fish were allocated into twelve tanks for four treatments, receiving diets containing 0, 100, 250, and 500 mg/kg HE for eight weeks. The results showed that dietary HE supplementation induced no significant differences in the growth performance, feed efficiency, and hematological parameters (P > 0.05). HE supplementation significantly increased total leukocyte count and the highest count was observed in 250 mg/kg HE treatment (P < 0.001). Fish in 250 and 500 mg/kg HE treatments exhibited significantly lower lymphocyte (P = 0.001) and higher neutrophil (P = 0.002) percentages; the former exhibited a significantly higher monocyte percentage (P = 0.021). Hepatic superoxide dismutase (100 and 250 mg/kg HE; P < 0.001), glutathione peroxidase (100 and 250 mg/kg HE; P = 0.001), glutathione reducatse (all HE treatments; P < 0.001), and reduced glutathione (250 mg/kg HE; P = 0.046) significantly increased, whereas hepatic malondialdehyde levels (250 and 500 mg/kg HE; P = 0.007) significantly decreased in HE-treated fish. Plasma total protein, albumin, globulin, lysozyme, and alternative complement significantly increased in 250 and 500 mg/kg HE treatments and plasma total Ig significantly increased in 250 mg/kg HE treatment. Quantitative real time PCR found no Streptococcus iniae, Lactococcus garvieae, Aeromonas hydrophila, Yersinia ruckeri, and Vibrio anguillarum in the fish intestines in any treatments. Lactobacillus sp. was detected in the fish intestinal samples, but there were no significant differences among the treatments (P = 0.352). Intestinal defensin (P = 0.044) and interleukin-1 beta (P = 0.0.035) expressions were significantly up-regulated in 100 mg/kg HE; intestinal interleukin-10 (P < 0.001) and tumor necrosis factor-alpha (P < 0.001) expressions were significantly up-regulated in 100 and 500 mg/kg HE; whereas, intestinal interleukin-6 expression was significantly (P = 0.009) up-regulated in 250 mg/kg HE treatments. It is concluded that HE is able to stimulate humoral and intestinal immune responses and hepatic antioxidant capacity. HE effective concentration in rainbow trout may be in the range of 100-250 mg/kg.